2014
DOI: 10.1016/j.amjsurg.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of complications following deceased donor liver transplant

Abstract: Background Liver transplantation is a complex surgery associated with high rates of postoperative complications. While national outcomes data are available, national rates of most complications are unknown. Data Sources A systematic review of the literature reporting rates of postoperative complications between 2002 and 2012 was performed. A cohort of 29,227 deceased donor liver transplant recipients from 74 studies was used to calculate pooled incidences were for 17 major postoperative complications. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 81 publications
(50 reference statements)
5
16
1
1
Order By: Relevance
“…Moreover, education of families is vital in ensuring the success of longer-term surveillance of patients in detecting complications of more delayed-onset. Our rates of wound infection (2.5%), wound dehiscence (2.1%) and incisional hernias (0.7%) were low and compared favorably with literature [3,9]. This low instance of wound infection may have been underreported, as this is usually a comparatively minor complication and hence less accurately recorded.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, education of families is vital in ensuring the success of longer-term surveillance of patients in detecting complications of more delayed-onset. Our rates of wound infection (2.5%), wound dehiscence (2.1%) and incisional hernias (0.7%) were low and compared favorably with literature [3,9]. This low instance of wound infection may have been underreported, as this is usually a comparatively minor complication and hence less accurately recorded.…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, the use of split and other marginal liver grafts, either from a cadaveric or living related donor, allows for timely transplantation, reducing wait list morbidity and mortality [10]. Postoperative morbidity in children arises owing to a number of contributing factors including pretransplant morbidity, such as malnutrition, graft type and quality, previous abdominal procedures, surgical and anesthetic expertise and postoperative management [9]. Bowel perforation has a reported incidence between 2.5% and 20% and a related high mortality rate of 30%-50% [11][12][13][14][15], making early diagnosis and appropriate postoperative management essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McElroy and associates 11 recently published an excellent meta-analysis. This analysis of 29 227 recipients of deceased-donor liver transplants from 74 studies identified 17 types of postoperative complications.…”
Section: Funda Atar Et Al/experimental and Clinical Transplantation (mentioning
confidence: 99%
“…They also stated that the postoperative pneumonia rate could be reduced by systematic and intensive pulmonary rehabilitation, described in general surgery patients. 11 Almost one-quarter of the analyzed studies were associated with pulmonary complications, with these studies stating that the complications could be prevented by rehabilitation. As in the meta-analysis, our series also identified pneumonia as the main cause of ARF.…”
Section: Funda Atar Et Al/experimental and Clinical Transplantation (mentioning
confidence: 99%